KNOWLEDGE AND ATTITUDES OF PREGNANT WOMEN IN IMMUNIZING TETANUS TOXOID AT BOTANIA PUSKESMAS, BATAM CITY - Tafsil Tafsil; Muhammad Rifki (Universitas Batam, 2020)
Background : Tetanus is still a leading cause of maternal and neonatal death and illness. Immunization of TT (Tetanus Toxoid) which is a process of building immunity as an effort to prevent tetanus infection. The estimated global incidence of tetanus is 18 per 100,000 population per year. The purpose of this study was to determine the relationship between knowledge and attitudes of pregnant women in immunizing Tetanus Toxoid. Method : The research method used was an analytic survey with a cross sectional approach. Conducted at Puskesmas Botania, Batam City, the study was conducted for 6 months, the population in this study were all trimester III primigravida pregnant women, with a sample of 30 respondents, using a total sampling technique. Data collection using a questionnaire. Data presented in tabular and textual form, data analysis using Chi-square. Result : The results of the study of 30 respondents found that 20 respondents (66.7%) had less knowledge about TT immunization, it was found that 19 respondents (63.3%) had negative attitudes, based on bivariate analysis using chi-square. From the Chi-Square test with a significance limit (Î±) = 0.05 and the result of p-value = 0.000 which means p-velue <(Î±). Conclusion : It is said that the two variables have a relationship or Ha is accepted, this means that there is a relationship between maternal knowledge and attitudes. in carrying out TT immunization at the Botania Health Center, Batam City. Research suggestions for pregnant women increase knowledge about TT immunization so that mothers comply with TT immunization